INTERNET OF THINGS IMPLEMENTATION IN HIGH FREQUENCY MEASUREMENTS - Selva Rajoo, Kukaneswaran (IRC, 2019)

(untitled)
With a vision of advancing into Industry 4.0, emerges an obligation for the industry to appreciate and participate in the global change. Industry 4.0 focuses mainly on the application of Internet of Things (IOT), Cyber-Physical System, and Smart Factory. These applications can push forward the industry in terms of productivity through the implementation of automation of daily operation. In this study, the primary focus is on the application of Internet of Things in the testing and measurement field. The current high frequency measuring instruments are incapable of adapting into the idea of Industry 4.0 since they could not be operated remotely and are unable to exchange data via cloud servers. In the aspects of data analysis, the instruments are unable to model the device under test (DUT)’s behaviour as there is no competent post-processing tool to analyse the measurement results. With regards to the mentioned concerns, this study aims to wirelessly retrieve data without accessing the measuring and testing instruments. The user interface developed through Windows Presentation Foundation (WPF) is also able to communicate with the cloud server for data exchange. Data analysis tools would be integrated into the user interface to perform advanced analysis on the DUT’s behaviour through data post-processing. Thus Rohde & Schwarz Vector Network Analyzer as the counterpart instrument as well as WPF are thoroughly explored to study the feasibility of the idea and the methodology of this project. Required tests are conducted to ensure the deliverables are in par with the objective and requirements to be fulfilled.